ENDOSCOPIC ASSESMENT OF UPPER GASTROINTESTINAL SYSTEM IN PATIENTS WITH CHRONIC RENAL FAILURE - Osman ONAT; Ali DEMİR and Hüseyin ÇELİKER and Cemal LÜLECİ and Ahmet YILDIRIM and Hüseyin Cahit ELMACI (Turkish Journal of Gastroenterology, 2020)
-